1994
DOI: 10.1111/j.1755-3768.1994.tb05008.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary argon laser trabeculoplasty vs pilocarpine II: Long‐term effects on intraocular pressure and facility of outflow

Abstract: In a prospective study 82 patients recently diagnosed with simple or capsular glaucoma were randomized to receive primary argon laser trabeculoplasty or pilocarpine treatment. A 2-year follow-up showed a better success rate in the laser group, with less need for additional therapy. The average intraocular pressure and peak pressure was lower and the daytime pressure variation was significantly less in the laser group. The better increase in facility of outflow in the laser group was not statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Primary LTP has long been discussed (The glaucoma laser trial (GLT) 1990; Bergeå et al. 1994), and it is definitely an alternative, particularly if there is reason to avoid eye drops, such as in elderly patients who have difficulties applying that type of medication.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Primary LTP has long been discussed (The glaucoma laser trial (GLT) 1990; Bergeå et al. 1994), and it is definitely an alternative, particularly if there is reason to avoid eye drops, such as in elderly patients who have difficulties applying that type of medication.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…In Moorefields Primary Treatment Trial, IOP reduction was 14 mmHg after 6 monhts, but from a high average pre-treatment level of 35 mmHg. 16 Other investigators [17][18][19][20][21][22][23][24][25] have published values ranging from 5.9 to 12.1 mmHg. There are three possible explanations for these differences:…”
Section: Discussionmentioning
confidence: 99%
“…Considering the small number of eyes with exfoliation glaucoma in our material, it is obvious that non-significant findings might be explained by insufficient statistical power regarding exfoliation status. Many studies have shown that IOP reduction is larger in exfoliation glaucoma than in POAG, 2,5,19,22,32,38 even after performing multivariate analyses to correct for differences in pre-ALT IOP between these two types of the disease. 3 There is no agreement as to whether the pressure-lowering effect of ALT is influenced by trabecular pigmentation or pigmentation grade, 3 -5,22,24,37,38 and we found no significant impact of either of those aspects in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In previously untreated POAG patients, a 63.5% increase in tonographic outflow facility was measured with a 33% reduction in IOP [58]. A similar study on patients already on topical therapy showed a comparable 64% increase in outflow facility and 29% reduction in IOP [59].…”
Section: Aqueous Dynamics Of Laser Trabeculoplastymentioning
confidence: 66%